Scientometric analysis of Journal of Studies in Islamic Law & Jurisprudence: thematic map and co-authorship - Hossein Moradimoghaddam; Rouhallah Khademi (مطالعات فقه و حقوق اسلامی)
Scientometrics deals with the quantitative and qualitative analysis of scientific texts. One of the applications of Scientometrics is drawing a scientific map, which is done with different techniques such as co-word and co-authorship analysis. The current research was carried out to examine the Journal of Studies in Islamic Law & Jurisprudence with a scientometrics approach. The research method is of an applied type using the scientometric method with social network analysis techniques. The articles published in the Journal of Studies in Islamic Law & Jurisprudence from the beginning of publication until now (2010-2023) have been analyzed. The data analysis showed that, in total, from 2010 to 2023, 356 articles of this journal were indexed in the ISC database. To draw a thematic map, the co-occurrence technique of words was used. According to the centrality indicators, concepts such as civil responsibility, limit, right, freedom of opinion, apostasy, empowerment, cancellation, and jurisprudence, are among the most used topics in the articles of this journal. Examining the co-authorship network from the articles published in this journal showed that many co-authorship clusters were not formed. Most of the formed clusters have two members and there is only one cluster with 9 authors and two clusters with 3 authors. Examining the degree centrality showed that Mohammad Abu Ata took first place with a degree score of 8, and Mohammad Moloudi and Mehdi Hamzah Hoveyda took second and third places with 7 and 6, respectively. These authors have the highest amount of scientific cooperation with other authors. Examining the betweenness showed that Abu Atta with a betweenness of 18 took the first place, and Zulfaqari and Masjed Sarai were ranked second and third with 15 and 12, respectively. The scientific cooperation network of different universities in the form of co-authorship in the publication of articles in this journal showed that the researchers of Semnan University and Tehran University had the most connections with other universities. The research results also showed a significant relationship between the number of authors and the number of received citations.